Morphometric &Histological Study of the Adrenal Gland of the Adult female Rabbit (Orycotolagus Cuniculus) - Ahmed Obaid Hossain (Al-Qadisiyah Journal of Pure Science, 2018)
The aim of this study was to investigate the structure of the female rabbit adrenal gland by light  microscopic observations. For this purpose, ten adrenals were collected from five adult female rabbits. The tissues were processed for light microscopy. The weight of rabbit gave mean values of  2.04k g  and the mean values of long axis of left adrenal gland 15.46mm and the diameter of right gave mean values 11.30mm. The adrenal glands sit at the top of the kidneys,one on each side of the body, and have an inner core (known as the medulla) surrounded by an outer shell (known as the cortex). The adrenal cortex consists of three anatomic zones: the outer zona glomerulosa,; the intermediate zona fasciculata, which secretes cortisol; and the inner zona reticularis. The adrenal medulla, lying in the center of the adrenal gland, is functionally related to the sympathetic nervous system and secretes the catecholamines epinephrine and norepinephrine in response to stress.